The Family Value of Information, Community Support, and Experience Study: Rationale, Design, and Methods of a "Family-Centered" Research Study. Issue 12 (December 2015) - Reeves, Gloria M.; Wehring, Heidi J.; Connors, Kathleen M.; Bussell, Kristin; Schiffman, Jason; Medoff, Deborah R.; Tsuji, Thomas; Walker, Jane; Brown, Alicia; Strobeck, Danielle; Clough, Tammy; Rush, Caitlin B.; et al.
Abstract : Abstract: The Patient Protection and Affordable Care Act focuses on improving consumer engagement and patient-centered care. This article describes the design and rationale of a study targeting family engagement in pediatric mental health services. The study is a 90-day randomized trial of a telephone-delivered Family Navigator services versus usual care for parents of Medicaid-insured youth younger than 13 years with serious mental illness. Youth are identified through a pediatric antipsychotic medication preauthorization program. Family Navigators offer peer support to empower and engage parents in their child's recovery. Outcomes include parent report of empowerment, social support, satisfaction with child mental health services, and child functioning as well as claims-based measures of psychotherapy service utilization and antipsychotic medication dosage. The focus on "family-centered" care in this study is strongly supported by the active role of consumers in study design and implementation.